Beyond Instagram: Aspect-based sentiment analysis and cross-platform opinion mining in Philippine tourism user-generated content - Bejoc, Marites B.; Gorro, Ken D.; Olivar, Gladies Mae C.; Campita, Rose Ann Casas (Edelweiss Applied Science and Technology, 2025)
This study examines how diverse social media platforms contribute uniquely to the promotion of Philippine tourism destinations through user-generated content (UGC), moving beyond the Instagram-centric focus of previous research. Using a mixed-methods approach that combines quantitative content analysis, platform analytics, and qualitative surveys, this research analyzes UGC patterns across Instagram, TikTok, YouTube, Google Reviews, TripAdvisor, and travel blogs for five popular Philippine tourist destinations over a 12-month period. The study reveals significant platform differentiation in content types, audience engagement, and influence on travel decisions within the Philippine tourism context. TikTok emerged as the primary driver for spontaneous travel decisions among Gen Z Filipino and international travelers, with 78% of survey respondents indicating this platform's influence. Google Reviews maintained the strongest influence on accommodation and restaurant choices, with an 89% consultation rate. YouTube travel vlogs demonstrated the highest conversion rate for island-hopping and adventure travel planning, with 34% of viewers booking featured Philippine destinations within six months. While Instagram maintains the largest volume of Philippine tourism content, its influence on actual booking decisions is declining, functioning more as a visual inspiration tool. The research identifies a "platform ecosystem effect," where successful Philippine destinations leverage complementary strengths across multiple platforms rather than concentrating efforts on a single channel. These findings suggest that Philippine tourism marketers should adopt platform-specific content strategies rather than cross-posting identical content, with implications for the Department of Tourism's budgets and destination marketing campaigns.